Cerebral hemodynamic effects of early blood pressure lowering after TIA and stroke in patients with carotid stenosis. Issue 10 (December 2022) - Mazzucco, Sara; Li, Linxin; McGurgan, Iain J; Tuna, Maria Assuncao; Brunelli, Nicoletta; Binney, Lucy E; Rothwell, Peter M
Background: Effects of early blood pressure (BP) lowering on cerebral perfusion in patients with moderate/severe occlusive carotid disease after transient ischemic attack (TIA) and non-disabling stroke are uncertain. Aims: We aimed to evaluate the changes in transcranial Doppler (TCD) indices in patients undergoing blood pressure lowering soon after TIA/non-disabling stroke. Methods: Consecutive eligible patients (1 November 2011 to 30 October 2018) attending a rapid-access clinic with TIA/non-disabling stroke underwent telemetric home blood pressure monitoring (HBPM) for 1 month and middle cerebral artery velocities measurements ipsilateral to carotid stenosis on TCD ultrasound in the acute setting and at 1 month. Hypertensive patients (HBPM ⩾ 135/85) underwent intensive BP-lowering guided by HBPM unless they had bilateral severe occlusive disease (⩾ 70%). Changes in BP and TCD parameters were compared in patients with extracranial moderate/severe carotid stenosis (between 50% and occlusion) versus those with no or mild (< 50%) stenosis. Results: Of 764 patients with repeated TCD measures, 42 had moderate/severe extracranial carotid stenosis without bilateral severe occlusive disease. HBPM was reduced from baseline to 1 month in hypertensive patients both with versus without moderate/severe carotid stenosis (−12.44/15.99 vs −13.2/12.2 mmHg, respectively, p-difference = 0.82), and changes in TCD velocities (4.69/14.94 vs 2.69/13.86 cm/s, respectively, p-difference = 0.52 for peak systolic velocity and 0.33/7.06 vs 1.75/6.84 cm/s, p-difference = 0.34 for end-diastolic velocity) were also similar, with no evidence of greater hemodynamic compromise in patients with stenosis/occlusion. Conclusion: There was no evidence of worsening of TCD hemodynamic indices in patients with moderate/severe occlusive carotid disease treated with BP-lowering soon after TIA/non-disabling stroke, suggesting that antihypertensive treatment in this group of patients is safe in the acute setting of TIA clinics.